The Impact of Human Resource Management Practices, Organizational Culture, Motivation and Knowledge Management on Job Performance with Leadership Style as Moderating Variable in the Jordanian Commercial Banks Sector - raheem Ali Alsheikh, Ghaith Abdul raheem; Theeb Alnawafleh, Enas Ali; Abd Halim, Mutia Sobihah Binti; A Tambi, Abdul Malek Bin A (Journal of Reviews on Global Economics, 2018)
Abstract: In this paper, the effect of three human resource management practices namely, compensation and benefits, training and development, and performance appraisal and achievement was examined along with organizational culture, motivation and knowledge management on job performance among Jordanian banks. The construct of job performance was measured by the combination of task performance and organizational citizenship behavior. The study employed convenience sampling to which 30 questionnaires were distributed. The finding showed a significant impact of human resource management practices (compensation and benefits, training and development, and appraisal and achievement), organizational culture, motivation and knowledge management on job performance in the Jordanian banks. On the basis of the findings, the researcher provided recommendations for the banks in terms of strengthening the relationship between their knowledge management job performance. The study also provided implications to theory and practice based on the findings.Â